Meaning of Iconology in the Mural Painting Titled 'Last Supper' by Samson Gadikui - Colette, Barnerd Butit; Muhammad Khairullah, Muhammad Marzidi; Rahah, Hasan (Tuijin Jishu/Journal of Propulsion Technology, 2024)
This study delves into an in-depth analysis of Samson Gadikui's "Last Supper" mural located at St. Michael's Church in Penampang, Sabah. The objective is to unravel the artist's nuanced integration of symbolism, composition, and cultural adaptation to convey profound religious messages. The methodology encompasses a comprehensive approach, involving visual analysis, comparisons with art historical precedents, and consideration of cultural and historical contexts. The research unfolds in distinct phases, progressing through pre-iconography, mid-iconography, and final iconography, aiming to dissect the layers of meaning embedded in the mural. Results highlight Gadikui's mastery, emphasizing the mural's role as a visual sermon that invites viewers to engage with its theological and spiritual dimensions. The conclusion underscores the enduring significance of religious narratives in art, recognizing Gadikui's contribution to this tradition. The study's limitations include its reliance on a single observational instance, potential changes over time, lack of direct artist input, and limited engagement with existing literature. Additionally, empirical data on the mural's impact on the local community is absent. Future research should address these constraints for a more comprehensive understanding. Recommendations for future research advocate for an exploration of the mural's impact on the local community and a comparative analysis with other religious murals, seeking a broader understanding of visual representations of religious themes across diverse cultural contexts. This study contributes to the fields of art history, religious studies, and cultural anthropology by providing a nuanced examination of the mural's artistic and theological significance within a specific cultural and religious setting.